Entanglements of loneliness and mental ill health among young adult women - Anna Reetta Rönkä; Vappu Sunnari; Anja Taanila (International Journal of Qualitative Studies on Health and Well-being, 2020)
Purpose If a person experiences both loneliness and mental ill health, it may have severe effects on a person’s wellbeing and functioning. This study explored the ways in which loneliness may be entangled with mental ill health and the factors that contribute to the development of such entanglements. Methods The study participants were women from the Northern Finland Birth Cohort 1986 study, who, in 2001–2002, responded to the survey about being very lonely at the age of 15–16. Women (n = 17) were interviewed again at age 27–28 with semi-structured interviews. Data was analysed with thematic analysis. Results Loneliness and mental ill health formed four types of entanglements: Entanglement 1 (E1): “Loneliness periodically evoked depressive feelings”; E2: “Loneliness and depressive feelings formed an ongoing spiral”; E3: “Loneliness and diagnosed depression/serious emotional disturbance formed periodic spirals;” and E4: “Serious emotional disturbance/mental illness and loneliness formed an ongoing, difficult spiral.” Social adversities like unsafe family environment, lack of close friends, and school violence contributed to the development of Entanglements 1–3. In Entanglement 4, serious mental health disorder caused loneliness. Conclusions Loneliness was centrally linked to mental health issues in the present study and should be taken into consideration when providing mental health prevention and treatment.